Anthropometry and throwing velocity in elite water polo by specific playing positions - Ferragut, C.; Abraldes, J. A.; Vila, H.; Rodriguez, N.; Argudo, F. M.; Fernandes, R. J. (Journal of Human Kinetics, 2011)
The purposes of this study were threefold: to present the specific physical structure of elite water polo players by playing positions, to access its throwing velocity in different conditions (without goalkeeper, with goalkeeper and with previous displacement), and to observe the relationships between the assessed anthropometric and throwing velocity parameters. Nineteen water polo players of the Spanish National Team (nine offensive wings, five center back and five center forwards) were evaluated. The anthropometric profile (particularly the lengths, breaths, girths and skinfolds) was obtained according to the International Working Group of Kinanthropometry, and the throwing velocity was assessed in 3 x 2 maximal intensity shoots (3 min interval) from the penalty line using a radar. It was possible to observe higher values of body mass, BMI, and muscle mass of the center forwards compared to the wings, and foot length of the center backs compared with the wings, reflecting a specific physical profile for each playing position. However, no difference was found between groups regarding the breadths values. In addition, the somatotype of the wings is a balanced mesomorph, and the center backs and center forwards endo-mesomorphs. Despite center backs have higher hand grip values in comparison with wings, no differences were observed between specific playing positions in each throwing condition, as well as between conditions in each specific playing position. Moreover, observing the correlation coefficient values between anthropometric and throwing velocity variables by specific position for the three throwing conditions, a higher number of relationships was found for the center backs and center forwards rather than for the wings. When the total sample was analysed, a superior number of relationships was observed between the studied parameters in throwing with goalkeeper situation. These data reflects the dependence of the throwing skill on the anthropometric characteristics of water polo players.